MANAJEMEN KELAS DALAM MENINGKATKAN KEDISIPLINAN SISWA KELAS VIII SMP N 1 AGRABINTA KABUPATEN CIANJUR - Yayi Solihah; Sri Retno; Dinny Mardiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Classroom management is a crucial aspect in creating an effective and positive learning environment. With effective classroom management, students can feel comfortable, engaged, and motivated to learn, thereby creating optimal conditions for achieving learning objectives. This research uses qualitative field research with a qualitative case study approach. A case study is a detailed examination of a single setting, a single subject, a document repository, or a specific, clearly defined event or case, whether it be an individual, family, or organization. The research findings indicate that: The implementation of classroom management at SMP N 1 Agrabinta was carried out effectively and efficiently by establishing class agreements, creating clear rules, and developing planned and regular lesson schedules to improve student learning discipline. Additionally, by providing consistent support and guidance to students, teachers can create a structured and positive learning environment.